Exploring Factors Causing Traffic Congestion through Average Index Method: A Case Study of Hyderabad City - Fahad Ahmed Shaikh; Nafees Ahmed memon; Imtiaz Ahmed chandio (Pakistan Journal of Engineering Technology & Science)
The rapid growth in population and economic activity has primarily led to increased traffic congestion. The system of managing and planning transportation triggers chaos. The study aims to determine the major factors behind Traffic congestion. High urbanization rate, encroachments, public dependency upon private vehicles and giving of public transport, Lack of awareness, and monitoring of transportation adequacy, etc. In this regard, hotspot areas are highlighted, and the factors are ranked, which are assessed using a Likert scale rating-based questionnaire conducted by experts and respondents of Hyderabad, Sindh. These factors are analyzed by applying the Average Index Method Technique, and the sites are identified by generating the Road Network maps on ArcGIS. Findings reveal a clear concept about traffic congestion and the factors blocking traffic flow in the study area. It further explores that the top-ranked factor for traffic congestion, with an average index of 4.50, is Encroachments on roads and Footpaths, whereas the lowest average index is 3.30, Location of Hospitals and other amenities near main roads. This research can help reduce traffic congestion in Hyderabad and other cities with similar scenarios.